AN ANALYSIS OF UNIT SHIFT AND STRUCTURE SHIFT FOUND IN A LITTLEPRINCESS NOVELBY FRANCESS HODGSON BURNETT - Situmorang, Kesiana Tetriwan; Afriana, Afriana (LPPM Universitas Putera Batam, 2019)
This research is entitled as An Analysis of Unit Shift and Structure Shift Found in a Little Princess Novel by Frances Hodgson Burnett. The purpose of this research is to analyze the types of unit shift and structure shift. The theory used in this research based on translation shift theory by Catford (1965). The method is qualitative descriptive. And the method of collecting data is used documentation. Some steps in documentation. They are read the novel, observed the translation word by word, sentence by sentence and search the data. The researcher search the unit shift and structure shift, sort the unit shift and structure shift in draft of data then, classify between unit shift and structure shift. This research used words in describing the result. The result of this research are 51 items data. In unit shift, phrase into word are 10 data, word into clause are 5 data, word into sentence is 1 data, phrase into sentence are 2 data, phrase into clause are 8 data. And structure shift, simple sentence are 10 data, compound sentence are 5 data, complex sentence are 7 data, complex compound sentence are 3 data. The conclusion are unit shift can changed one word meaning as source language to phrase as target language, also unit shift changed clause in source language to sentence in target language. And structure shift can used “and, also, whatever, for combine dependent clause and independent clause.